Early Onset Neonatal Group B Streptococcal Sepsis - Oh, William (American Journal of Perinatology, 2013)
Early onset neonatal group B streptococcal (GBS) sepsis is a serious neonatal illness with high morbidity and mortality. The disease can present in two forms: early clinical manifestation with respiratory distress soon after birth or late presentation with gradual onset of signs of sepsis. The former carries a high risk for serious cardiovascular complication with persistent pulmonary hypertension; the latter is often complicated with meningitis that may lead to serious neurodevelopmental impairment. An important advance in the past three decades is the development and implementation of preventive strategy for this disease by universal screening and identification of maternal GBS carriers and/or risk factors with subsequent use of intrapartum antibiotic prophylaxis. The strategy has resulted in a significant reduction of the disease from 1.5 to 0.3/1,000 live births over the past three decades. Some women may have unknown GBS status. The American Academy of Pediatrics has developed an algorithm as guidance for the management of the newborns.
Keywords: neonatal sepsis; chorioamnionitis; intrapartum antibiotic prophylaxis; GBS screening